Synthesis and theoretical characterization of ternary Cux(Ge30Se70)100-x glasses - Saeedy, H. I. El; YakouT, H. A.; Aly, K. A.; Saddeek, Y. B.; Dahshan, A.; Sidek, H. A. A.; Matori, K. A.; Zaid, M. H. M.; Zakaly, H. M. H. (Elsevier BV, 2021)
The Cux(Ge30Se70)100−x (0 ≤ x ≤ 12 at.%) chalcogenide alloys have been synthesized by the conventional melt quenching technique. The physical properties such as the mean coordination number, density, molar volume, compactness, overall bond energy, and cohesive energy were estimated for the Cu doped Ge-Se glassy alloys. The chemical bond approach (CBA) was used to predict the type and proportion of the formed bonds in the studied glasses. Subsequently, several structural and physical properties have been estimated. The results show that the studied glasses are rigidly connected, having an average coordination number increase from 2.6 to 2.77. The density and glass compactness show an increase with the Cu content, whereas the main atomic volume decreases. The cohesive energy and the heat of atomization show a similar behavior trend with the enhancement of Cu % in the Ge-Se binary glasses. The optical band gap was estimated theoretically compared with the previously published experimental values for the Cux(Ge30Se70)100−x (0 ≤ x ≤ 12 at.%) thin films. The covalency parameter >91% for the studied glasses so that the compositions may be used as a stable glass former. Furthermore, the mechanical properties as the elastic bulk modulus, Poisson’s ratio, Young’s modulus, micro-hardness, and Debye temperature were investigated as a function of the Cu content.